Vimentin Tail Segments Are Differentially Exposed at Distinct Cellular Locations and in Response to Stress - Lois-Bermejo, Irene; González-Jiménez, Patricia; Duarte, Sofia; Pajares, María A.; Pérez-Sala, Dolores (Frontiers in Cell and Developmental Biology, 2022)
The intermediate filament protein vimentin plays a key role in cell signaling and stress sensing, as well as an integrator of cytoskeletal dynamics. The vimentin monomer consists of a central rod-like domain and intrinsically disordered head and tail domains. Although the organization of vimentin oligomers in filaments is beginning to be understood, the precise disposition of the tail region remains to be elucidated. Here we observed that electrophilic stress-induced condensation shielded vimentin from recognition by antibodies against specific segments of the tail domain. A detailed characterization revealed that vimentin tail segments are differentially exposed at distinct subcellular locations, both in basal and stress conditions. The 411-423 segment appeared accessible in all cell areas, correlating with vimentin abundance. In contrast, the 419-438 segment was more scantily recognized in perinuclear vimentin and lipoxidative stress-induced bundles, and better detected in peripheral filaments, where it appeared to protrude further from the filament core. These differences persisted in mitotic cells. Interestingly, both tail segments showed closer accessibility in calyculin A-treated cells and phosphomimetic mutants of the C-terminal region. Our results lead us to hypothesize the presence of at least two distinct arrangements of vimentin tail in cells: an “extended” conformation (accessible 419-438 segment), preferentially detected in peripheral areas with looser filaments, and a “packed” conformation (shielded 419-438 segment), preferentially detected at the cell center in robust filaments and lipoxidative stress-induced bundles. These different arrangements could be putatively interconverted by posttranslational modifications, contributing to the versatility of vimentin functions and/or interactions.